2017
DOI: 10.1002/jsfa.8749
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in nanotechnology transforming the agricultural sector: a transition replete with opportunities

Abstract: The applications and benefits of nanotechnology in the agricultural sector have attracted considerable attention, particularly in the invention of unique nanopesticides and nanofertilisers. The contemporary developments in nanotechnology are acknowledged and the most significant opportunities awaiting the agriculture sector from the recent scientific and technical literature are addressed. This review discusses the significance of recent trends in nanomaterial-based sensors available for the sustainable manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(97 citation statements)
references
References 250 publications
(492 reference statements)
0
94
0
3
Order By: Relevance
“…The remaining player in this new ‘Big Four’ structure is BASF. Although the company is the largest in terms of overall revenues among the companies in this grouping, its percentage of crop protection sales stands at ‘only’ $7 billion …”
Section: Ecofriendly Considerations For a New Agrochemical Eramentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining player in this new ‘Big Four’ structure is BASF. Although the company is the largest in terms of overall revenues among the companies in this grouping, its percentage of crop protection sales stands at ‘only’ $7 billion …”
Section: Ecofriendly Considerations For a New Agrochemical Eramentioning
confidence: 99%
“…Although the company is the largest in terms of overall revenues among the companies in this grouping, its percentage of crop protection sales stands at 'only' $7 billion. 31 So, as a result of an increase of reports on environmental contamination, toxic effects on biota and plant pathogen and pest resistance by chemical pesticides, new agrochemicals characterized by improved formulations and new delivery mechanisms will be developed. In particular, a new era of agrochemicals appears to be related to the use of biodegradable nanoscaled materials as a vehicle to active ingredients (AIs) characterized by antimicrobial activity as biopesticides.…”
Section: Ecofriendly Considerations For a New Agrochemical Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a wide range of nanotechnology applications has been intensively studied in the agriculture research sector developing practices at both academic and industrial levels [4][5][6]. In fact, nanotechnology has the potential to improve the entire current agricultural and food industry, by developing new tools for plant disease treatments [7], pathogen detection [8], and improving the ability of plants to absorb nutrients [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Du et al [14] represented that the ZnO-NPs were more significantly effective on the germination and growth of wheat rather than ZnSO 4 . In addition, they showed that ZnSO 4 was more toxic than ZnO-NPs at higher dosages.…”
Section: Introductionmentioning
confidence: 99%